The Photon - Drag Effect in Rectangular Quantum Wire with An Infinite Potential - Hoang, Van Ngoc (H. : ĐHQGHN, 2017)
The photon - drag effect with optical phonon-electron scattering in rectangular quantum wire with an infinite potential is studied. Based on the quantum kinetic equation for electrons under the action of a linearly polarized electromagnetic wave, a dc electric field and an intense laser field, analytic expressions for the density of the direct current for the case of electron – optical phonon scattering are calculated. The dependence of the direct current density on the frequency W of the laser radiation field, the frequency w of the linearly polarized electromagnetic wave, the size of the wire is obtained. The analytic expressions are numerically evaluated and plotted for a specific quantum wire, GaAs/AlGaAs. All these results of quantum wire are compared with bulk semiconductors and superlattices to show the differences.